Mealtime caregiving approaches and behavioral symptoms in persons living with dementia: a longitudinal, observational study - Ji Yeon Lee; Kyung Hee Lee; Eleanor S. McConnell (BMC, 2021)
Abstract Background Behavioral symptoms during mealtime can prohibit persons living with dementia from obtaining sufficient nutrition. However, little research has examined the relationship between behavioral symptoms and caregiving approaches. This study examines this relationship and further explores which specific caregiver behaviors were related to behavioral symptoms among persons living with dementia. Methods A secondary data analysis was performed using 86 mealtime videos from a longitudinal, observational study. The videos were repeatedly taken at months 0, 3, and 6 with 30 persons living with dementia in one of four long-term care facilities. Video coding was performed using coding schemes modified from the Cohen-Mansfield Agitation Inventory for behavioral symptoms and the Person-/Task-Centered Behavior Inventory for caregiving approaches. Coding schemes for behavioral symptoms consisted of four categories: total duration, aggressive behavior, physically nonaggressive behavior, and verbally agitated behavior. Caregiving approaches consisted of ten-verbal/seven-nonverbal person-centered behavior codes, four-verbal/four-nonverbal task-centered behavior codes, and no-verbal/no-nonverbal interaction codes. A mixed-effect model was conducted using variables such as demographics, medical information, cognitive status, depression, function, and caregiving approaches as fixed effects, participant as a random effect, and four categories of behavioral symptoms as dependent variables. Results The total duration of the Cohen-Mansfield Agitation Inventory was associated with no verbal response (β = 9.09) and task-centered verbal behavior (β = 8.43), specifically verbal controlling (β = 7.87). Physically nonaggressive behavior was associated with no verbal response (β = 9.36). Verbally agitated behavior was associated with task-centered nonverbal behavior (β = 51.29), and specifically inappropriate touch (β = 59.05). Conclusions Mealtime is indispensable to dementia care for ensuring adequate nutrition and promoting personhood. Our findings revealed caregivers' task-centered behaviors and no interaction were related to behavioral symptoms of persons living with dementia. When caregivers encounter behavioral symptoms during mealtime, it is recommended to avoid no response and task-centered behaviors, especially verbal controlling and inappropriate touch, and to promote person-centered behaviors.